Engaged and insurgent scholarship: a reflection - Ntsebeza, Lungisile (Review of African political economy, 2024)
This article is a rejoinder to the special issue that celebrates and honours my life as a scholar-activist. Rather than directly responding to the articles, the rejoinder traces my intellectual and political development from growing up in Cala, a small village town where I was born in the Eastern Cape, to how I ended up being the engaged and insurgent scholar that all the contributors proclaim me to be. The key point is that my entry into the academic world and where I am now can be traced to my involvement in organic, community-based reading and study groups in Cala and beyond, thus underscoring an almost seamless continuity in my intellectual and political work. Related to this is a reminder that rigorous intellectual activity does not happen only in the academy. None of the activists in our study groups was an academic. The flow of knowledge is not one-directional, where knowledge generated from the academic is transmitted to the wider world. Academics should accept that there is a lot they can learn from intellectual activities taking place outside the academy. Hence the importance of greater collaboration between university-based academics and intellectuals who are doing serious work outside the academy. Finally, this rejoinder is a clarion call to academics for engaged and insurgent scholarship: making a connection between their scholarly pursuits and the struggle for social and economic justice. The call is not about academics and intellectuals acting for and on behalf of the downtrodden, but rather for academics to conduct rigorous research using the abundant resources in academic institutions and feed its outcomes back in intelligible forms to the wider society as a way of developing the agency of the downtrodden to lead struggles for emancipating not only themselves, but society at large.